2020
DOI: 10.1093/tbm/ibz146
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the scalability of the collaborative care model for depression using mobile technology

Abstract: The collaborative care model (CoCM) has substantial support for improving behavioral health care in primary care. However, large-scale CoCM adoption relies on addressing operational and financial implementation challenges across health care settings with varying resources. An academic medical center serving socioeconomically and racially diverse patients implemented the CoCM in seven practices. A smartphone application was introduced to facilitate CoCM care management during depression treatment (app-augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…A total of 20 studies were included in this review. The characteristics of the studies are summarized in Table 1, and more details on individual studies are provided in Multimedia Appendix 2 [15,35,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The 20 studies included a comparative effectiveness trial of an interactive voice recording (IVR) intervention in a safety net population and a series of post hoc analyses on the same study population [41][42][43][44], a randomized trial of an internet support group with an associated subgroup analysis [45,46], 30% (6/20) other randomized trials [35,[47][48][49][50][51][52], a nonrandomized trial [53], 25% (5/20) implementation trials without a comparator [15,[54][55][56][57], and a qualitative exploratory study [58].…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 20 studies were included in this review. The characteristics of the studies are summarized in Table 1, and more details on individual studies are provided in Multimedia Appendix 2 [15,35,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. The 20 studies included a comparative effectiveness trial of an interactive voice recording (IVR) intervention in a safety net population and a series of post hoc analyses on the same study population [41][42][43][44], a randomized trial of an internet support group with an associated subgroup analysis [45,46], 30% (6/20) other randomized trials [35,[47][48][49][50][51][52], a nonrandomized trial [53], 25% (5/20) implementation trials without a comparator [15,[54][55][56][57], and a qualitative exploratory study [58].…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…Most studies identified by this review implemented or assessed multiple technologies at once rather than a single intervention. Of the 20 studies, 5 (25%) [15,50,53,54,57,58] assessed mobile apps, and 5 (25%) used a web-based platform [46,[49][50][51][52]. Adewuya et al [47] and Jin and Wu [48] used SMS text messaging as a core feature of the intervention, although other investigators used SMS text messaging as an adjunctive tool [51,53,59].…”
Section: Digital and Mobile Health Technologies In CCmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 20 studies, 1 (5%) described a decision support tool to triage patients into different levels of care [52]. Studies also used technology to facilitate measurement-based care by collecting clinical assessments [48,51,53,54]. Most studies provided participants with self-management modules and psychoeducational materials [15,35,46,[49][50][51]53,54,57].…”
Section: Digital and Mobile Health Technologies In CCmentioning
confidence: 99%